2014
DOI: 10.1159/000358508
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stent, but Not Bare Metal Stent, Accentuates the Systematic Inflammatory Response in Patients

Abstract: Objective: The systematic pro-inflammatory responses after percutaneous coronary intervention with drug-eluting stents (DES) remain poorly defined. Therefore, we compared the systematic pro-inflammatory state of circulating mononuclear cells (MNCs) between DES and bare metal stent (BMS) implantation. Methods: Patients with indications for treatment with stents were randomized in a 1:1 ratio to placement of DES or BMS. The primary endpoint was a change of pro-inflammatory state at 12 weeks post-procedure. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…NF-kB DNA binding activity was measured with NF-kB transcription factor assay kit (Abcam) according to the manufacturers' instructions. 20 Short interfering RNA transfection in MNCs. Human short interfering-sirtuin 1 (si-SIRT1) and mock short interfering RNA (siRNA) were obtained from Santz Cruz Biotechnology, and transient siRNA transfection was carried out according to the protocol of the manufacturer as described previously.…”
Section: Translational Significancementioning
confidence: 99%
“…NF-kB DNA binding activity was measured with NF-kB transcription factor assay kit (Abcam) according to the manufacturers' instructions. 20 Short interfering RNA transfection in MNCs. Human short interfering-sirtuin 1 (si-SIRT1) and mock short interfering RNA (siRNA) were obtained from Santz Cruz Biotechnology, and transient siRNA transfection was carried out according to the protocol of the manufacturer as described previously.…”
Section: Translational Significancementioning
confidence: 99%
“…DES-induced inflammatory reaction has been found as early as 30 days after implantation but progressed in frequency and severity through 90 to 180 days in porcine model [ 1 ]. Furthermore, our previous studies found that DES implantation induced specific systematic inflammatory state, as evidenced by the enhanced NF- κ B activity, suppressed PPAR- γ activity, and elevated plasma inflammatory factors, compared with no-stent implantation or bare metal stent (BMS) implantation [ 4 , 5 ]. However, how to refine DES-induced proinflammation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, possible systemic anti inflammatory effects of DES, besides their local effects, were emphasized again [15] . In 2014, Liu et al published a research about the same subject with the new generation stents [9] . Thirty six stable patients were randomised in 1:1 manner to everolimus type DES and BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been published data about the prolonged and pronounced systemic inflammatory response triggered by DES, in contrary to their local anti-inflammatory properties [9] . When we have a consensus and exact data in this topic in the future, we may prescribe much intense anti-inflammatory regimens such as higher dose statins for the patients with DES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation